Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Guru Di SMP Negeri 1 Gampengrejo Kabupaten Kediri - Ike Yuliatus Sholikah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of the variables work discipline (X1) and work motivation (X2) on teacher performance (Y) at SMP Negeri 1 Gampengrejo, Kediri Regency. This type of research is quantitative research. The data collection techniques used are primary data and secondary data. The sample selection used the saturated sampling method, the number of samples in the study was 52 respondents at SMP Negeri 1 Gampengrejo, Kediri Regency. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The research results showed that the multiple linear regression equation Y = 1.349 + 0.369 The F test results obtained Fcount results with a significance value of 0.000 < 0.05. From the results of the analysis it can be concluded that work discipline and work motivation have a significant simultaneous effect on teacher performance at SMP Negeri 1 Gampengrejo, Kediri Regency.